A Study on the Ability of Different Non-Intrusive Sensors for Diagnosing Outdoor Insulator Defects - Kumru, Celal Fadil; Lutfi, Abdulla; El-Hag, Ayman; Darwish, Ahmad; Refaat, Shady S.; Abu-Rub, Haitham (Electrical Insulation Conference and Electrical Manufacturing Expo, 2023)
Insulators' failures caused by any type of defect may result in serious technical and economic losses. In particular, contamination flashovers due to excessive pollution and humidity are one of the main problems encountered in power systems. Moreover, other types of defects like surface crack and internal void are other common examples of outdoor insulator defects that may lead to insulator failure. In this regard, detecting the defect using a non-intrusive method is important in terms of energy continuity and monitoring efficiency. Both vision (regular, IR and UV camera) and emission (RF, ultrasonic, and acoustic) based sensors have been deployed in the field to detect these defects. It has been reported that each sensor has certain pros and cons in terms of its ability to detect the different defects. Therefore, it is essential to investigate and compare the sensing performance of non-intrusive sensors for different defects. In this study, an ultrasonic sensor (20 - 100 kHz), an RF antenna (0.53 - 3 GHz) and an IR camera were used to detect dry band arcing, corona and surface discharge. All three sensors along with the standard partial discharge measurement system were used simultaneously for each measurement. The results show that sensing performance of the three sensors varies depending on the defect type.